The inhibition of seed germination treated with water extract of sorghum (Sorghum bicolor, L.) cultivated in Histosols - Susilo, E.; Setyowati, N.; Nurjannah, U.; Riwandi; Muktamar, Z. (International Journal of Agricultural Technology, 2021)
Allelopathy is a form of suppressing plant growth due to the release of toxins into the surrounding plants. Sorghum (Sorghum bicolor, L.) is a plant producing an allelopathic compound. Abiotic stress to sorghum planted in Histosols can determine the allelochemical release process. Application of an aqueous sorghum extract can control weeds nearby the main crop. The inhibition of seed germination treated with water extract of sorghum grown in marginal lands (Histosols) with different pattern of water application is determined. A watering pattern consisted of wet, alternate of a week wet and dry pattern, alternate of a week dry and wet pattern, dry and Ultisols (as a control). The concentration of root water extract of sorghum consisted of 0.0%, 2.5%, 5.0%, 7.5%, 10.0%, 15.0%, 20.0%, and 25.0%. The results showed that the highest inhibition of sorghum seed germination was under 7.5-10% concentration of water extract at dry Histosols as indicated by the lowest plumula and radicle fresh and dry weight. This finding indicated that drought stress sorghum in Histosols produces the highest allelopathic compound. Therefore, the plant has the potential as a source of bioherbicides.